2007
DOI: 10.1007/s10886-006-9233-6
|View full text |Cite
|
Sign up to set email alerts
|

Differential Attraction of Heliothis subflexa Males to Synthetic Pheromone Lures in Eastern US and Western Mexico

Abstract: The mate attraction signal of Heliothis subflexa (Hs) females consists of a multicomponent sex pheromone blend. In this study, we assessed the intraspecific importance of three groups of compounds found in Hs pheromone glands: three acetate esters (Z7-16:OAc, Z9-16:OAc, and Z11-16:OAc), two 14-carbon aldehydes (14:Ald and Z9-14:Ald), and one 16-carbon alcohol (Z11-16:OH). Because the relative importance of pheromone components may vary in different regions, we conducted experiments in Eastern US (North Carolin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 55 publications
0
41
0
Order By: Relevance
“…a Summarized from Roelofs et al (1974), Tumlinson et al (1975Tumlinson et al ( , 1982, Klun et al (1979Klun et al ( , 1980, Vetter and Baker (1983), Ramaswamy et al (1985), Teal et al (1986), and Vickers and Baker (1997). b Summarized from Teal et al (1981), Klun et al (1982), Heath et al (1990), and Groot et al (2007). Jurenka, 2003;Choi et al, 2005), followed by the QTL found in Sheck et al (2006) (BCs old) and in this study.…”
Section: Introductionmentioning
confidence: 50%
“…a Summarized from Roelofs et al (1974), Tumlinson et al (1975Tumlinson et al ( , 1982, Klun et al (1979Klun et al ( , 1980, Vetter and Baker (1983), Ramaswamy et al (1985), Teal et al (1986), and Vickers and Baker (1997). b Summarized from Teal et al (1981), Klun et al (1982), Heath et al (1990), and Groot et al (2007). Jurenka, 2003;Choi et al, 2005), followed by the QTL found in Sheck et al (2006) (BCs old) and in this study.…”
Section: Introductionmentioning
confidence: 50%
“…Male response to varying sex pheromone blends was assessed in field trapping experiments in Clayton, NC, using Heliothis mesh traps arranged in a completely randomized block design (see Groot et al 2007 for more details). Two synthetic lure experiments were done, where the relative amount in the lure was varied of the: 1) critical secondary sex pheromone component Z9-tetradecenal (Z9-14:Ald) and 2) compound hexadecanal (16:Ald).…”
Section: Methodsmentioning
confidence: 99%
“…Groot et al (2007) suggested that monitoring with traps using pheromones is a key strategy for integrated C. subflexa management programs. It is noteworthy that chemical management must be focused on the adult insect once the caterpillars are protected by the calyx in the larval stage.…”
Section: A B Cmentioning
confidence: 99%
“…It occurs in tropical and subtropical regions of the American continents in the following countries: United States, Canada, Mexico, Jamaica, Puerto Rico, Cuba, Nicaragua, Costa Rica, Panama, Trinidad and Tobago, Colombia, Ecuador, Venezuela, Peru, Argentina, Bolivia and Brazil (Heath et al, 1990;Poole et al, 1993;Bado et al, 2005;Groot et al, 2007;Groot et al, 2009;Pogue, 2013;De Souza et al, 2015). The areas of occurrence in Brazil include the Amazon, Northeastern region (Pernambuco, Paraíba), Southeastern (Rio de Janeiro) and Midwestern regions (Mato Grosso do Sul; Goiás) (Poole et al, 1993;De Souza et al, 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation